Tuning of electrocatalytic properties of MoS2 by chalcogenide ion implantation. (March 2019) - Luxa, Jan; Mazánek, Vlastimil; Mackova, Anna; Malinsky, Petr; Akhmadaliev, Shavkat; Sofer, Zdeněk
Graphical abstract: Highlights: Molybdenum disulfide crystals were implanted by sulfur, selenium and tellurium. Ion beam implantation with selenium and tellurium led to the reduction of hydrogen overpotential. Sulfur implantation is accompanied with surface oxidation and increase of hydrogen evolution overpotential. Abstract: MoS2 is one of the most explored and promising material for electrocatalytic water splitting by hydrogen evolution reaction (HER). However, in its bulk form, MoS2 possesses only poor activity towards HER. Therefore, appropriate treatment has to be employed to tune its catalytic properties. In this study, we report the influence of ion bombardment (S, Se and Te ions) with medium ion energy (400 keV) and various ion fluences (1 × 10 14 –1 × 10 16 ions/cm 2 ) on the electrocatalytic properties of bulk MoS2 crystals. Our results showed that upon irradiation, sulfur vacancies were created. Upon exposure to ambient atmosphere, sulfur vacancies were partially replaced by oxygen, which led to surface oxidation. Nevertheless, samples irradiated using the higher range of ion fluences have generally showed enhanced catalytic HER performance in comparison with untreated MoS2 crystals. Furthermore, we have also demonstrated that ion irradiation/implantation can serve as a tool for doping of MoS2 crystals with Se and Te which can also influence the HER performance. The reported results demonstrate that ion beam irradiation can be used for doping as well as creation of sulfur vacancies in bulk MoS2 crystals which is fundamental for the HER performance.